Pengaruh Kualitas Produk, Cita Rasa dan Kemasan Produk terhadap Keputusan Pembelian Ampyang : (Survei Pada Perusahaan Ampyang Pak Mino di Kecamatan Pracimantoro) - Royan Saputra; Sumaryanto Sumaryanto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The purpose of this research is to analyze (1) the significance of the influence of product quality on purchasing decisions at Ampyang Pak Mino in Pracimantoro, (2) the significance of taste on purchasing decisions at Ampyang Pak Mino in Pracimantoro, (3) the significance of product packaging on purchasing decisions at Ampyang Pak Mino in Pracimantoro. The sample for this research is an unknown number of buyers of Ampyang Pak Mino. The population of this study was 100 people. The data collection technique for this research uses a questionnaire. The data analysis technique used is multiple regression analysis, t test, F test and coefficient of determination test (R2). The research results show that: (1) product quality has a significant influence on purchasing decisions at Ampyang Pak Mino in Pracimantoro, (2) taste has a significant influence on purchasing decisions at Ampyang Pak Mino in Pracimantoro, (3) product packaging has a significant influence on purchasing decisions at Ampyang Pak Mino in Pracimantoro.